CPCSEA Inspections: Can it be done the AAALAC way? (Journal of Laboratory Animal Science, 2024)
India is one of the countries which have oldest regulations  for animal welfare and experimentation. The Committee for  the Purpose of Control and Supervision of Experiments on  Animals (CPCSEA) was constituted by the Government of  India, way back in 1968 under chapter IV of the Prevention  of Cruelty to Animals (PCA) Act, 1960 to oversee the animal  experiments and welfare.
Keywords: internationally; Handbook; inspection